2015
DOI: 10.1007/s12012-015-9326-y
|View full text |Cite
|
Sign up to set email alerts
|

Losartan Inhibits Vascular Calcification by Suppressing the BMP2 and Runx2 Expression in Rats In Vivo

Abstract: The blockade of renin-angiotensin II system has been shown to reduce morbidity and mortality in hypertension, atherosclerosis, diabetes and chronic kidney disease. Since vascular calcification (VC) is commonly found in these diseases, the aim of this study was to examine whether or not losartan, a widely used angiotensin II receptor blockers, inhibits VC in rats in vivo. A rat model of VC was generated by treating rats with a combination of warfarin and vitamin K1. Two weeks after the treatments, the rats were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Numerous studies, including our previous work, have shown that paracrine/autocrine factors are involved in vascular calcification and many agents could modify vascular calcification, including sodium pyrophosphate, 50 lanthanum carbonate, 51 angiotensin II receptor blocker losartan, 52 and the bioactive peptide adrenomedullin. 12 IMD has several benefits for inhibiting vascular calcification.…”
Section: Discussionmentioning
confidence: 98%
“…Numerous studies, including our previous work, have shown that paracrine/autocrine factors are involved in vascular calcification and many agents could modify vascular calcification, including sodium pyrophosphate, 50 lanthanum carbonate, 51 angiotensin II receptor blocker losartan, 52 and the bioactive peptide adrenomedullin. 12 IMD has several benefits for inhibiting vascular calcification.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown that VC is cell-mediated and inactive process, which may result from the osteogenic differentiation of VSMCs and subsequent extracellular matrix mineralization (28)(29)(30). Runx2, which is a central transcription factor, is necessary for osteogenic matrix gene expression, bone formation, VSMC calcification and differentiation (22,31,32). Furthermore, the increasing phosphate concentration in vitro results in upregulation of Runx2 expression and downregulation of smooth muscle-specific gene expression (10).…”
Section: Discussionmentioning
confidence: 99%
“…When rabbits fed an atherogenic diet to induce atherosclerosis and arterial calcification are administrated with an ARB, calcification together with expression of BMP2 and osteocalcin are attenuated (33). Rats treated with warfarin and vitamin K with or without AT 1 R blocker losartan also demonstrate that the ARB reduces aortic calcification with suppression of BMP2 and Runx2 (570). ANG II also upregulates the receptor activator of NF-B ligand (RANKL) system in VSMCs, which is known to increase BMP2 expression, and bone-related genes cbfa1 and msx2, which cumulatively promote vascular calcification, and enhanced ACE expression and AT 1 R mRNA in vivo.…”
Section: Ang II Mechanisms Of Arterial Stiffnessmentioning
confidence: 99%